A new species of Chthonerpeton (Amphibia: Gymnophiona: Typhlonectidae) from Rio de Janeiro, Brazil - Santos, Rodolfo Otávio; Pineschi, Renato Balieiro; Zaher, Hussam (Zootaxa, 2025)
Caecilian amphibians (Gymnophiona) are characterized by their snake-like bodies and secretive habits. Although most of them are predominantly terrestrial and fossorial as adults, the family Typhlonectidae includes species well-adapted to aquatic and semi-aquatic lifestyles. Among typhlonectids, Chthonerpeton is the most speciose genus and occurs mainly along the east coast of South America. Here we describe a new species of Chthonerpeton from Itaboraí, Rio de Janeiro, Brazil. The new taxon is similar to C. perissodus and C. braestrupi but can be readily diagnosed from them and all other congeners by a unique combination of features traditionally used for diagnosing species of the genus (e.g., position of the tentacles, dentition, body shape and proportions, color pattern, number of annuli and vertebrae). We also provide a taxonomic key to the ten currently recognized species of Chthonerpeton and discuss the implications of the newly described species for the systematics of this genus of Neotropical caecilians.